A Note on the Modified q-Bernstein Polynomials - Taekyun Kim; Lee-Chae Jang; Heungsu Yi (Discrete Dynamics in Nature and Society)
We propose the modified q-Bernstein polynomials of degree n which are different q-Bernstein polynomials of Phillips (1997). From these modified q-Bernstein polynomials of degree n, we derive some recurrence formulae for the modified q-Bernstein polynomials.